The Effect of Technology-Assisted Speaking Practice on English Pronunciation and Speaking Skills at SMPN 2 Bantan - Siti Khotijah; Masrul; Ramdhan Witarsa (ASIAN: Indonesian Journal of Learning Development and Innovation, 2024)
This study aims to examine the effect of technology-assisted speaking practice on English pronunciation and speaking skills at SMPN 2 Bantan. The method used in this study is an experiment with a non-equivalent control group design. The population in this study were grade VIII students at SMPN 2 Bantan, with samples taken randomly. The instruments used in this study included a speaking skills test and a pronunciation skills test. The results showed that there was a significant effect of technology-assisted speaking practice on improving students' English pronunciation and speaking skills. Students who participated in technology-assisted speaking practice showed higher improvements compared to students who did not participate in the practice. In addition, technology-assisted speaking practice also increased students' confidence in communicating using English. This study provides implications that the use of technology in English learning can be an effective strategy to improve students' language skills. It is recommended that teachers use technology more in the learning process to create a more interactive and interesting learning environment.